Time course of dementia following sepsis in German health claims data. Issue 1 (January 2021) - Fritze, Thomas; Doblhammer, Gabriele; Widmann, Catherine N.; Heneka, Michael T.
Abstract : Objective: We evaluated the short-, medium-, and long-term effects of sepsis on dementia incidence using German health claims data. Methods: A total of 161, 567 patients (65 years or older) were followed from 2004 to 2015 at quarterly intervals. Time since sepsis was categorized into 0 (the effective quarter of sepsis diagnosis), 1–8, and ≥9 quarters since the latest diagnosis of sepsis, taking into account admission to intensive care unit and controlling for delirium, surgery, age, sex, and comorbidities. Incident dementia was defined for all persons who did not have a validated dementia diagnosis in 2004 and 2005 and who received a first-time, valid diagnosis between 2006 and 2015. Results: During the quarter of sepsis diagnosis, patients not admitted to intensive care had a 3.14-fold (95% CI 2.83–3.49) increased risk, and those with intensive care stay had a 2.22-fold (95% CI: 1.83–2.70) increased risk of receiving an incident dementia diagnosis compared with patients without sepsis. The impact of sepsis on incident dementia remained in the following 2 years, remitting only thereafter. Conclusions: For sepsis survivors, medium-term dementia risk remains elevated, whereas long-term risk may reach the level of those without sepsis, even after controlling for delirium. These findings encourage identifying modifiable components of hospital and rehabilitation care.